Association between joint hypermobility and pelvic organ prolapse in women: a systematic review and meta-analysis. Issue 10 (October 2016) - Veit-Rubin, Nikolaus; Cartwright, Rufus; Singh, Anand; Digesu, G.; Fernando, Ruwan; Khullar, Vikram
Abstract Introduction and hypothesis Abnormalities of common collagen proteins have been noted in individuals affected by POP and JHM, suggesting a common aetiology. We assessed strength, consistency and potential for bias in pooled associations of the relationship between JHM and POP. Methods We searched MEDLINE, EMBASE and CINAHL, as well as International Continence Society (ICS) and International Urogynaecologic Association (IUGA) annual meeting abstracts, including reference lists, without language restrictions. We included case–control and cohort studies and applied strict criteria for choosing eligible studies. Methodologically trained reviewers independently screened abstracts and full texts to confirm eligibility. We extracted data on study and patient characteristics, clinical assessment tools, and methodology. We assessed comparability and representativeness of source populations, confidence in the assessment of JHM and POP and adjustment for confounding and missing data. Meta-analysis was performed using a random effects model. Results We retrieved 39 full texts, of which 14 were used in the meta-analysis. Overall pooled odds ratio (OR) was 2.37 [95 % confidence interval (CI) 1.54–3.64, I2 = 77.0 %]. We identified no significant factors in meta-regression, and there was no evidence of publication bias; six studies were at high risk of bias with frequent differences in sampling frames, limited validity for clinical assessments and failure to match for important prognostic variables. Conclusions We found a strong association between POP and JHM, with an effect size that is clinically relevant. Our findings are limited by high heterogeneity and the potential for residual confounding factors. JHM is an important early indicator for POP risk, and future longitudinal studies should explore the shared aetiology.